Critical thinking of student nurses during clinical accompaniment - BY Uys; SM Meyer (AOSIS, 2005)
The purpose of this study was to investigate the methods of clinical accompaniment used by clinical facilitators in practice. The findings of the study also reflected facilitators' perceptions regarding critical thinking and the facilitation thereof. A quantitative research design was used. A literature study was conducted to identify the methods of accompaniment that facilitate critical thinking. Data was collected by means of a questionnaire developed for that purpose. Making a content-related validity judgment, and involving seven clinical facilitators in an academic institution, ensured the validity of the questionnaire. The results of the study indicated that various clinical methods of accompaniment were used. To a large extent, these methods correlated with those discussed in the literature review. The researcher further concluded that the concepts 'critical thinking' and 'facilitation' were not interpreted correctly by the respondents, and would therefore not be implemented in a proper manner in nursing practice. Furthermore, it seemed evident that tutor-driven learning realised more often than student-driven learning. In this regard, the requirement of outcomes-based education was not satisfied. The researcher is therefore of the opinion that a practical programme for the development of critical thinking skills during clinical accompaniment must be developed within the framework of outcomes-based education.